Antimicrobial effect of probiotic microorganisms onclinical and standard Staphylococcus aureus isolates - RAYAMAN, PERVİN; RAYAMAN, ERKAN (My University, 2023)
In this study we aimed to identify probiotic microorganisms in various pharmacy preparations, market and homemade probiotic products and investigate the antimicrobial effect of these microorganisms on clinical and standard Staphylococcus aureus isolates. The probiotic microorganisms were isolated from probiotic products mentioned above, then identified by Matrix Assisted Laser Ionization Mass Spectrophotometer (MALDI-TOF, Biomeriux) and also by conventional methods. The tolerance of these probiotic microorganisms to different salt, pH and temperature conditions was also detected. The antimicrobial activity of the specified probiotic microorganisms on S. aureus was designated by using spot on lawn and agar well diffusion methods. In our study among 16 probiotic products, 27 various probiotic microorganisms were specified by MALDI-TOF. Additionally, 15 of these probiotic microorganism species had an isolated reliability value above 90%. In our study 10 probiotic microorganism species, 7 of which were different from each other were found to maintain their viability in three various pH, salt and temperature conditions. These probiotic microorganisms were Lactobacillus rhamnosus (P.2 probiotic pharmaceutical product), Enterococcus gallinarum (homemade whey), Lactobacillus kefiri 1 (homemade kefir), Bacillus megaterium (homemade pickled juice), Lactobacillus kefiri 2 (homemade kefir), Lactobacillus rhamnosus (P.1 company preparation) Lactobacillus plantarum (P.3 company preparation), Bifidobacterium spp (M.4 company pure kefir), Enterococcus faecium (P.3 company preparation). We determined that Lactobacillus plantarum isolated from homemade whey had the highest antimicrobial activity on clinical MRSA 3 (Methicillin resistant Staphylococcus aureus) strain (inhibition zone =45.62 mm ± 0.84. Also, we have found that, probiotic microorganisms isolated from pharmacy preparations, market and homemade probiotic products showed antibacterial effect on clinical and standard Staphylococcus aureus by spot on lawn method. We designated that besides probiotic microorganisms isolated from various pharmacy preparations, probiotic microorganisms isolated from market and homemade products were efficient against clinical and standard S. aureus isolates
Keywords: Probiotic products; antimicrobial activity; probiotic microorganisms; Staphylococcus aureus; spot on lawn